PENGEMBANGAN MEDIA KOMIK BRILIAN BERBASIS PEMBELAJARAN MULTILITERASI - Rizkiyani, Nurafiah; Syachruroji, Ahmad; Setiawan, Sigit (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
This study aims to develop a learning product in the form of Brilliant Comics based on Multiliteracy learning for Grade IV Elementary School. The place of this development research is at SD Negeri Kembangan Utara 09. The subjects of this research are fourth grade elementary school students. The research model used is the Research & Development model from Sugiyono (2015). While the data collection techniques through interviews, preliminary studies, questionnaire collection, and documentation. Brilliant Comic Media has passed the validation stage with an average percentage score of 90.75% from the media expert team in the